Evaluation of outcomes in patients with pancreatic cancer and Human Immunodeficiency Virus at Chris Hani Baragwanath Academic Hospital and the Donald Gordon Medical Centre, Johannesburg - Wing, Jessica Roberta (My University, 2024)
Background: Cancers which are not associated with Acquired Immune Deficiency Syndrome (AIDS) are increasing in incidence and mortality in the HIV-positive population. Pancreatic cancer (PC) is projected to be the second most common cause of cancer-related death by 2030. No literature exists on patients with PC and concomitant human immunodeficiency virus (HIV) infection in South Africa (SA), which has the highest number of HIV-positive people in the world. Objectives: To compare the demographics, stage, histological grade of disease, and survival outcomes of HIV-positive compared to HIV-negative patients diagnosed with PC. Methods: Records of patients diagnosed with PC were collected from Chris Hani Baragwanath Academic Hospital (CHBAH) and the Wits Donald Gordon Medical Centre (DGMC) from the 1 st of January 2013 to the 31st of December 2018. A total of 240 patients’ records were obtained. Demographic, clinical, and survival data were collected. Results: There were predominantly black Africans (64.6%) and males (54.6%) in the study. Although overall survival between the HIV-positive and negative patients did not differ (p=0.051), the median time of survival from presentation was significantly shorter in the HIV-positive compared to the HIV-negative patients (2.1 months; IQR 1.2-6.0 vs. 4.7 months; IQR 1.6-13.0; p=0.017). The HIV-positive cohort presented at a significantly younger age compared to the negative cohort (54.6; ±9.6 vs 62.4; ±11.1; p=0.0001) and at a more advanced stage of disease (72.2% vs. 43.1%; p=0.017). No difference was found between the histological grade of PC in both cohorts (p=0.298). The median survival time for HIV-positive patients on therapy at presentation was significantly longer compared to patients who were not (3.0; IQR 1.3-7.8 vs 1.1 months; IQR 0.9-1.9; p=0.037). Overall survival in patients who underwent pancreaticoduodenectomy at Wits DGMC was shown to be higher compared CHBAH V (41.7% vs. 12.5%; p=0.049). The majority of the patients presented with regionally advanced (30.6%) and metastatic (50.3%) disease. Conclusion: This is the first study in SA to provide insight into the clinical disease profile and survival outcomes of HIV-positive patients diagnosed with PC. This study has shown that HIV-infected patients with PC have a specific disease profile. Therefore, testing for HIV infection should be included in the management of all patients with PC, a higher index of suspicion for cancer should be maintained in younger HIV-positive patients and initiation of Antiretroviral treatment (ART) must be timeous.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Medicine (MMed) in Internal Medicine to the Faculty of Health Sciences, University of the Witwatersrand, School of Clinical Medicine, Johannesburg, 2023
Keywords: Cancer; Pancreatic cancer; HIV-positive population; SDG-3: Good health and well-being; SDG-16: Peace, justice and strong institutions